Guideline of the Swiss Society of Gynaecology and Obstetrics (SSGO) on acute and recurrent urinary tract infections in women, including pregnancy (Swiss Medical Weekly, 2020)
Acute and recurrent urinary tract infections (UTIs) are common auto-infectious diseases transmitted from the intestinal tract. They affect the urinary tract either through recurrence or through persistence. The incidence of UTIs increases with age and comorbidities. In this guideline from the Swiss Society of Gynaecology and Obstetrics (SSGO), diagnosis and treatment of UTIs are grouped into uncomplicated and complicated cases. This is to our knowledge the first guideline that specifically considers UTIs in pregnancy and breastfeeding, and the prevention of UTIs in the context of urogynaecological diagnosis and surgery. Recommendations are based on observational, retrospective or randomised controlled studies. The level of evidence was rated according to recommendations made by the Oxford Centre of Evidence-based Medicine.In non-pregnant women and women